Distinctive features of Phox2b-expressing neurons in the rat reticular formation dorsal to the trigeminal motor nucleus. (1st September 2017) - Nagoya, Kouta; Nakamura, Shiro; Ikeda, Keiko; Onimaru, Hiroshi; Yoshida, Atsushi; Nakayama, Kiyomi; Mochizuki, Ayako; Kiyomoto, Masaaki; Sato, Fumihiko; Kawakami, Kiyoshi; Takahashi, Koji; Inoue, Tomio
Highlights: Phox2b -expressing (Phox2b + ) neurons are distributed in the reticular formation dorsal to the trigeminal motor nucleus (RdV). Almost all Phox2b + RdV neurons are excitatory, while Phox2b -negative (Phox2b − ) RdV neurons consist of a mixed population. Most of Phox2b + neurons show low-frequency firing without spontaneous activity, as opposed to the Phox2b − neurons. About half of Phox2b + and Phox2b − neurons are premotor neurons that target the trigeminal motoneurons. Phox2b + and Phox2b − RdV neurons may play important roles in feeding-related functions. Abstract: Phox2b encodes a paired-like homeodomain-containing transcription factor essential for development of the autonomic nervous system. Phox2b -expressing (Phox2b + ) neurons are present in the reticular formation dorsal to the trigeminal motor nucleus (RdV) as well as the nucleus of the solitary tract and parafacial respiratory group. However, the nature of Phox2b + RdV neurons is still unclear. We investigated the physiological and morphological properties of Phox2b + RdV neurons using postnatal day 2–7 transgenic rats expressing yellow fluorescent protein under the control of Phox2b . Almost all of Phox2b + RdV neurons were glutamatergic, whereas Phox2b -negative (Phox2b − ) RdV neurons consisted of a few glutamatergic, many GABAergic, and many glycinergic neurons. The majority (48/56) of Phox2b + neurons showed low-frequency firing (LF), while most of Phox2b − neurons (35/42) exhibited high-frequency firing (HF) in response to intracellularly injected currents. All, but one, Phox2b + neurons (55/56) did not fire spontaneously, whereas three-fourths of the Phox2b − neurons (31/42) were spontaneously active. K + channel and persistent Na + current blockers affected the firing of LF and HF neurons. The majority of Phox2b + (35/46) and half of the Phox2b − neurons (19/40) did not respond to stimulations of the mesencephalic trigeminal nucleus, the trigeminal tract, and the principal sensory trigeminal nucleus. Biocytin labeling revealed that about half of the Phox2b + (5/12) and Phox2b − RdV neurons (5/10) send their axons to the trigeminal motor nucleus. These results suggest that Phox2b + RdV neurons have distinct neurotransmitter phenotypes and firing properties from Phox2b − RdV neurons and might play important roles in feeding-related functions including suckling and possibly mastication.